The Marketing of Employee Volunteerism - Peloza, John (Journal of business ethics, 2009)
Employee volunteerism can be an effective strategy for increasing the effectiveness of corporate philanthropy. However, in order to be effective, volunteer initiatives should be directed by the firm to ensure a strategic fit and focus on the core competencies of the firm. Therefore, internal marketing strategies are needed to ensure managers receive employee support. Our research quantitatively extends research by Peloza and Hassay (Journal of Business Ethics 64(4), 357–379, 2006) who argued that employee volunteerism is motivated by egoistic, altruistic and organizational citizenship motives. Our findings suggest that volunteer opportunities that fulfill egoistic and organizational citizenship motives will be effective, but that the altruistic motive is not significant. We also find that formal policies concerning manager recognition or time off are not effective, providing more discretion for individual managers. Implications for managers seeking to increase the effectiveness (and therefore support the business case) of their corporate philanthropy are discussed.